Insight into the Structural, Electronic, Elastic, Mechanical, and Thermodynamic Properties of XReO (X = Rb, Cs, Tl) Perovskite Oxides: A DFT Study. - Zhao, Song; Wei, Zhongbin; Dar, Sajad Ahmad (Zeitschrift für Naturforschung Section A: A Journal of Physical Sciences, 2019)
In the present work, perovskite oxides XReO (X = Rb, Cs, Tl) have been reported using density functional theory (DFT) for structural, electronic, mechanical, elastic, and thermodynamic properties. Structural optimization has been carried out using local density approximation (LDA) and generalized gradient approximation (GGA) in the scheme of Perdew, Burke, and Ernzerhof. Electronic properties have been calculated using GGA, and all the three materials were found to have metallic nature. From the elastic constants, all the three compounds were found mechanically stable in cubic structure. Poisson's ratio (ν), Cauchy's pressure (C–C) and Pugh ratio (B/G) present the ductile nature of RbReO and TlReO, whereas CsReO was found to establish a brittle nature. These compounds were found to have an elastically anisotropic nature. The calculated melting temperatures were found to be 2851 ± 300, 2814 ± 300, and 2924 ± 300 K, respectively, for XReO (X = Rb, Cs, Tl). Using quasi-harmonic Debye approximation, we have calculated the pressure- and temperature-dependent variation in cell volume, bulk modulus, Debye temperature, and specific heat capacity.